PENDAMPINGAN CALON NASABAH DALAM PROGRAM EDUKASI TRADING VALBURY APPS DI PT. VALBURY ASIA FUTURES SURABAYA - Muhamad Rafli Pratama; Vian Ahmad Saputra (Education and Talent Development Center of Indonesia, 2025)
The purpose of this community service program is to discuss the Mentoring of Prospective Customers in the Valbury Apps Trading Education Program at PT. Valbury Asia Futures Surabaya which aims to improve the understanding and readiness of the community in entering the world of trading. This program is designed to provide comprehensive education to prospective customers through the introduction of the Valbury Apps application, basic trading training, and personal consultation sessions. Systematic assistance so that prospective customers can understand risk management and use of the platform properly before jumping directly into the real market. The results of this program show that education is very good for improving financial literacy and the confidence of prospective customers in making trading decisions independently. Thus, this program not only strengthens the relationship between the company and prospective customers but also becomes an effective strategy in building customers who are interested in the world of trading.